Geochemical analysis of Late Classic and Post Classic Maya marketplace activities at the Plazas of Cobá, Mexico. (February 2015) - Coronel, Eric G.; Hutson, Scott; Magnoni, Aline; Balzotti, Chris; Ulmer, Austin; Terry, Richard E.
<x content-type="archive" xml:space="preserve">Abstract</x> Lines of evidence for ancient exchange plazas may include trade routes and trade artifacts, urban open space near public structures, and rock alignments denoting market stalls, but regular patterns in soil chemical concentrations also point to marketplace use. We applied geochemical and geospatial analysis of the floors of the main Plaza of Group B and Plazas A, H, and J of Group D at Cobá, Mexico, to discover the chemical residues of phosphorus (P) and metals associated with the exchange of foodstuffs and mineral workshop items that may have been marketed there. The patterns of chemical residues in the floor of the Group B Plaza suggest ritual activities while the linear, parallel patterns of elevated Mehlich phosphorus and chelate extractable zinc concentrations in Plaza A support the hypothesis of market exchange at that location. Plaza H is associated with several Postclassic buildings, including the Pinturas Structure D-33. During the Postclassic period, Cobá had lost much of its population, though chemical residues from Plaza H are congruent with marketing. We argue that Plazas A and H were not permanent marketplaces but rather multi-purpose locations that also hosted large ceremonies.